How Does the Zoning System Policy Impact the Quality of Student Input on Islamic Elementary School? - Ulpah Maspupah; Dwi Priyanto (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2020)
This study aims to examine the impact of zoning system policy on schools under the auspices of Lembaga Pendidikan Ma'arif (LPM) Banyumas as well as differences in terms of prospective students’ physical-psychological readiness, the supporting capacity of prospective students’ parents, and the supporting capacity of the distance of prospective students’ house to school, after the implementation of the zoning system policy. This research is a descriptive qualitative in nature. The research subjects in this study are 13 Ma’arif Islamic elementary schools (Madrasah Ibtidaiyah/MI) under the auspices of the LPM in Banyumas. The research sample was determined using random sampling method, taking into account the level of relevance and representation. Data were collected through observation, interviews and documentation. The result shows that 1) the zoning system has indirect impact on the quality of student input at Islamic elementary schools under LPM Banyumas, 2) there has been difference in terms of prospective students’ physical-psychological readiness, the supporting capacity of prospective students’ parents, and the supporting capacity of the distance of prospective students’ house to school, before and after the implementation of the zoning system policy.